Sustainable Nanomaterials for Biomedical Applications - Yuhang Zhang; Kingsley Poon; Gweneth Sofia P. Masonsong; Yogambha Ramaswamy; Gurvinder Singh (MDPI AG, 2023)
Significant progress in nanotechnology has enormously contributed to the design and development of innovative products that have transformed societal challenges related to energy, information technology, the environment, and health. A large portion of the nanomaterials developed for such applications is currently highly dependent on energy-intensive manufacturing processes and non-renewable resources. In addition, there is a considerable lag between the rapid growth in the innovation/discovery of such unsustainable nanomaterials and their effects on the environment, human health, and climate in the long term. Therefore, there is an urgent need to design nanomaterials sustainably using renewable and natural resources with minimal impact on society. Integrating sustainability with nanotechnology can support the manufacturing of sustainable nanomaterials with optimized performance. This short review discusses challenges and a framework for designing high-performance sustainable nanomaterials. We briefly summarize the recent advances in producing sustainable nanomaterials from sustainable and natural resources and their use for various biomedical applications such as biosensing, bioimaging, drug delivery, and tissue engineering. Additionally, we provide future perspectives into the design guidelines for fabricating high-performance sustainable nanomaterials for medical applications.